2021
DOI: 10.3390/brainsci11111431
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Field Stimulation Attenuates Phasic Nociception after Complete Spinal Cord Injury in Rats

Abstract: Traumatic spinal cord injury (SCI) is one of the most incapacitating pathologies, leading to huge rehabilitation challenges besides a social-economic burden on SCI patients and their families. There is no complete curative treatment available so far. Non-invasive and patient-friendly use of extremely low-frequency electromagnetic field stimulation (EMF) has emerged as a therapeutic and rehabilitation option. In this study, we tested whole-body EMF stimulation on thoracic complete SCI-induced nociception includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Preclinical studies in complete and incomplete rat models of spinal cord injury have shown significant beneficial effects of external magnetic field exposure for 5–8 weeks on autonomic (urinary bladder) function, locomotion, sensorimotor and pain perception. The functional recovery observed is suggested to be due to attenuation of glial scaring, lesion volume, neurotransmitter imbalance and facilitation of neuronal survival and axonal regeneration (Pal et al 2013, 2018; Dey et al 2017; Bhattacharyya et al 2020; Kumar et al 2021) [ [44] , [45] , [46] , [47] , [48] ]. Application of iTBS for 2 weeks has also shown to facilitate cortical excitability and promote axonal regeneration in SCI rat model (Marufa et al 2021) [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies in complete and incomplete rat models of spinal cord injury have shown significant beneficial effects of external magnetic field exposure for 5–8 weeks on autonomic (urinary bladder) function, locomotion, sensorimotor and pain perception. The functional recovery observed is suggested to be due to attenuation of glial scaring, lesion volume, neurotransmitter imbalance and facilitation of neuronal survival and axonal regeneration (Pal et al 2013, 2018; Dey et al 2017; Bhattacharyya et al 2020; Kumar et al 2021) [ [44] , [45] , [46] , [47] , [48] ]. Application of iTBS for 2 weeks has also shown to facilitate cortical excitability and promote axonal regeneration in SCI rat model (Marufa et al 2021) [ 49 ].…”
Section: Discussionmentioning
confidence: 99%